STUDI KOMPARATIF PEMBERIAN EDUKASI TENTANG KESIAPSIAGAAN BENCANA GEMPA BUMI DENGAN MEDIA POWER POINT DAN VIDEO BERNYANYI TERHADAP PENGETAHUAN SISWA KELAS 4-5 DI SD KARANGGAYAM - Lala Budi Fitriana; Paulinus Deny Krisnanto; Nosi Glosia (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Comparative Study of Providing Education on Earthquake Disaster Preparedness with Power Point Media and Singing Videos on Knowledge of Class 4-5 Students At Karanggayam Elementary SchoolBackground: Knowledge is the basis or the beginning of one’s action and awareness, knowledge is crucial in taking disaster management actions. Objectives: This study aims to determine the knowledge before and after providing education about earthquake disaster preparedness using PowerPoint media to students in grades 4-5 Karanggayam Elementary School; and the knowledge before and after giving education about earthquake disaster preparedness using singing-video media to students in grades 4-5 Karanggayam Elementary School. Methods: This research method used a quasi-experimental design with pre-test and post-test nonequivalent groups. The respondents were selected using an accidental sampling technique. The number of samples were 30 respondents, divided into two groups, and each group consisted of 15 respondents. The research instrument used were questionnaire sheets. The data collected on the use of PowerPoint media and singing videos were both analyzed using a Bivariate analysis, they were assessed using the Wilcoxon test. Results: The median value for PowerPoint media was 16 before and became 17 after the intervention, the video singing median value was 17 before and became 16 after the intervention. The results of statistics tests before and after the intervention in the PowerPoint media group obtained a P value of 0.180, and in the video singing group, the P value was 0.131. Conclusion: There was no difference in the knowledge about earthquake disaster preparedness in the PowerPoint media group and the singing videos group.